Navigating Environmental Policy in North Bandung Area: Overcoming Implementation Barriers for Sustainable Governance - Abdullah, Muhammad Solihin; Rusli, Budiman; Darto, Darto (Universitas Teuku Umar, 2025)
This study aims to answer the question: